The Relationship between Fuctional Tests and Knee Muscles Isokinetic Parameters in Patients with Patellofemoral Pain Syndrome - Shahin Goharpey; Mansour Fakour; Vahid Khalesi; Anita E'mrani; Mohammad Ja'far Shaterzadeh (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Patellofemoral pain syndrome is the most prevalent problem involving25 percent of all knee disorders. Such problems might be lead to functional disabilities. The goal of this study was to evaluate the relationship between functional tests and Isokinetic parameters of knee muscles and subjective assessment of knee function in patellofemoral pain syndrome and to compare between patient and control group. Materials & Methods: In this analytical and case - control research fifteen normal subjects and 15 patients with patellofemoral pain syndrome were selected with purposive sampling method in performing two main levels of this study: 1- Functional tests (bilateral squat and step down test) which performed randomly with considering of repetitions per 30 seconds, within 3 minutes rest between them applied and followed by subjective assessment of knee function with Kujala questionnaire. 2- Isokinetic tests performed with Biodex dynamometer device, during 10 to 90 degree of knee flexion with two distinct speeds, 60 and 120 degree per second. Results: No relationship was found between functional tests and Isokinetic parameters in patient group, but we observed a low significant relationship between functional tests and subjective assessment in this group (r=0/47 for Squat test and 0/37 for Step down test). Moderate significant relationship was found between subjective assessment of knee function and functional Hamstring: Quadriceps ratio for knee flexion at 60 degree per second (r = - 0/58). All of the Isokinetic parameters of quadriceps muscle in patient group were lower than control group. Conclusion: As there were low correlation between Isokinetic strength measurement and functional tests and subjective assessment of knee function, it is not recommended using these methods of assessment interchangeable in patients with patellofemoral pain syndrome.